Malocclusion status among 15 years old adolescents in relation to fluoride concentration and area of residence - Byalakere Rudraiah Chandra Shekar; Shankarappa Suma; Sudarshan Kumar; Jagadeeswara Rao Sukhabogi; Bhadravathi Cheluvaiah Manjunath (Wolters Kluwer Medknow Publications, 2013)
Objectives: To compare the overall dental aesthetic index scores between rural and urban areas, males and females, and to correlate dental aesthetic index score with fluoride concentration in drinking water. Settings and Design: The study was cross sectional and conducted among 15 year old adolescents in the rural and urban areas of Nalgonda district, Andhra Pradesh, India (an endemic fluoride belt). Materials and Methods: Six out of 59 mandals in Nalgonda district were first selected by simple random sampling technique. Then 24 secondary schools were selected from these six selected mandals. All eligible grade X children from these sixteen rural and eight urban schools, having different fluoride concentrations in drinking water, selected by simple random sampling, were considered for the study. Dentofacial anomalies with criteria of dental aesthetic index were used for assessing malocclusion. The information on the dietary habits, orthodontic treatment history, parafunctional habits, continuous residence etc., was collected using a pre-designed questionnaire. The examination was carried out by three trained and calibrated dentists. The Dental Aesthetic Index (DAI) scores, in areas with below optimal, optimal and above optimal fluoride concentrations, between urban and rural areas were compared and analyzed using SPSS windows version 16. Results: The mean DAI scores, for the rural and urban population were 21.37 ± 5.845 (mean ± SD) and 22.26 ± 6.115, for males and females, it was 20.86 ± 5.100 and 22.70 ± 6.713 respectively. The mean DAI scores in areas with below optimal, optimal and above optimal fluoride concentration were 23.42 ± 7.205 (mean ± SD), 20.85 ± 4.658 and 19.93 ± 4.312 respectively. Conclusion: The prevalence and severity of malocclusion was more in urban than rural areas, more among females than males, and it decreased with increasing concentration of fluoride in drinking water.